How to ‘deconvolute’ lung evolution - the evolutionary origins of pulmonary physiology - Torday, John S. (Henry Stewart Talks, 2016)
Cortisol, lung surfactant and lung development, Continuum from phylogeny and ontogeny to homeostasis and repair, Functional genomic homology between SB and lung, PTHrP and normal lung development, PTHrP and gravity, The origins of life: cellular evolution, Oxygen/stretch and positive selection pressure, Lung PTHrP/R as ‘blue print’ for other terrestrial exaptations